Liposomal and CpG-ODN formulation elicits strong humoral immune responses to recombinant Staphylococcus aureus antigens in heifer calves - Reidel, Ivana Gabriela (2019)
Bovine mastitis caused by Staphylococcus aureus is a serious problem in dairy production and effective immunoprophylaxis is an unmet goal so far. The objective of this work was to assess the humoral immune response of heifer calves against two recombinant S. aureus antigens: Clumping factor A (ClfA) and Fibronectin Binding Protein A (FnBPA), formulated with a novel adjuvant based on cationic liposomes (Lip) and CpG oligodeoxynucleotides (CpG-ODN). Six groups of 6-8 months old heifer calves received three doses biweekly of antigens, formulated with Al(OH)3, liposomes, CpG-ODN or Lip + CpG-ODN. Animals also received a fourth dose after a year (day 410) and a booster before calving. The administration of Al(OH)3+FnBPA/ClfA and Lip + FnBPA/ClfA + CpG-ODN induced the highest specific IgG levels, after the first 3 doses and induced a fast increase of antibodies after the fourth dose. All the formulations stimulated the production of specific IgG1, after the third and fourth dose. Specific IgG2 for both proteins was only stimulated after the fourth dose by Lip + FnBPA/ClfA + CpG-ODN. Pre-calving immunisation with Lip + FnBPA/ClfA + CpG-ODN led to the highest IgG levels during the calving period and to the production of the IgG2 subclass. The formulation was also able to stimulate the highest antibody levels in milk, 30 and 45 days after pre-calving booster. The combination of liposomes and CpG-ODN as adjuvant for a subunit vaccine, together with the immunisation schedule described, induced a strong humoral immune response with production of specific IgG2. The formulation demonstrated to induce immune memory allowing the application of a single pre-calving booster to maintain high antibody levels throughout the period of increased susceptibility to intramammary infections.